Importance of E-services for Cultural Tourism - Eveline van Leeuwen; Peter Nijkamp (Tinbergen Institute, 2011)
Despite a busy lifestyle – or perhaps as a result of a stressful lifestyle – more people than ever before make leisure trips, sometimes for a long time but in many cases just for short periods. Modern telecommunication technology brings attractive tourist destinations directly into the living rooms of potential travellers, also destinations that would otherwise have been difficult to find, such as certain cultural heritage objects. In this contribution, we will address the relevance of e-services in urban cultural tourism. Its aim is to map out the relative drivers of cultural visitors to cities with a particular view on the importance of modern e-services in the tourist sector. We focus on three case-study cities: Amsterdam, Leipzig and Genoa. We use discrete choice models and factor analysis to analyse the preferences of tourists for cultural heritage and e-services. Interestingly, in all three cities, the most important group of tourists, the cultural heritage enthusiasts, are often international tourists. This stresses the importance of multilingual e-services in order to maximise their impact on cultural heritage visitors and the tourism sector in general. In addition, it is also important to note that certain e-services become more important for tourists from further away, such as online booking systems.
urn:NBN:nl:ui:31-1871/38523
Keywords: L83; L86; 330; Tourism; cultural heritage; e-services; ordered logit models; factor analysis; Kulturtourismus; Internet; Urlaubsverhalten; E-Business; Amsterdam; Leipzig; Genua